Assessing the respective contributions of dietary flavanol monomers and procyanidins in mediating cardiovascular effects in humans: randomized, controlled, double-masked intervention trial. Issue 6 (24th October 2018) - Rodriguez-Mateos, Ana; Weber, Timon; Skene, Simon S; Ottaviani, Javier I; Crozier, Alan; Kelm, Malte; Schroeter, Hagen; Heiss, Christian
ABSTRACT: Background: Flavanols are an important class of food bioactives that can improve vascular function even in healthy subjects. Cocoa flavanols (CFs) are composed principally of the monomer (−)-epicatechin (∼20%), with a degree of polymerisation (DP) of 1 (DP1), and oligomeric procyanidins (∼80%, DP2–10). Objective: Our objective was to investigate the relative contribution of procyanidins and (−)-epicatechin to CF intake–related improvements in vascular function in healthy volunteers. Design: In a randomized, controlled, double-masked, parallel-group dietary intervention trial, 45 healthy men (aged 18–35 y) consumed the following once daily for 1 mo: 1 ) a DP1–10 cocoa extract containing 130 mg (−)-epicatechin and 560 mg procyanidins, 2 ) a DP2–10 cocoa extract containing 20 mg (−)-epicatechin and 540 mg procyanidins, or 3 ) a control capsule, which was flavanol-free but had identical micro- and macronutrient composition. Results: Consumption of DP1–10, but not of either DP2–10 or the control capsule, significantly increased flow-mediated vasodilation (primary endpoint) and the concentration of structurally related (−)-epicatechin metabolites (SREMs) in the circulatory system while decreasing pulse wave velocity and blood pressure. Total cholesterol significantly decreased after daily intake of both DP1–10 and DP2–10 as compared with the control. Conclusions: CF-related improvements in vascular function are predominantly related to the intake of flavanol monomers and circulating SREMs in healthy humans but not to the more abundant procyanidins and gut microbiome–derived CF catabolites. Reduction in total cholesterol was linked to consumption of procyanidins but not necessarily to that of (−)-epicatechin. This trial was registered at clinicaltrials.gov as NCT02728466.